Никуда не уйти от любви: повести - Колесникова Наташа (Русский романс, 2003)
Экземпляры: аб. (2003) / Инвентарный номер: 47394 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 60 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44